Seepage Analysis and the Reservoir Water Pollution Potential under Vertical Dam Structure Planning - Dinar C. Istiyanto; Ika Wulandari; Shafan A. Aziiz; Rizaldi C. Yuniardi; Suranto; Yofan T.D. Harita; Affandy Hamid; Aloysius B. Widagdo (Journal of the Civil Engineering Forum, 2023)
A prospective resolution to the intricate predicaments of flooding, sanitation, and the availability of unprocessed water for the populace of Jakarta residents is the implementation of the coastal reservoir paradigm. This paradigm entails harnessing the latent capacity of the Cisadane River flow and its subsequent storage within a retention pond, and then subjecting it to reprocessing to serve as a viable source of raw water. The selection of a vertical seawall design was based on the objective of creating an effective barrier between the reservoir and the sea, while also considering several environmental factors. This design was selected with the aim of minimizing the need for extensive soil excavation and rock placement. However, it is important to note that the risks of construction failure associated with seepage under hydraulic structure and dam stability pose significant challenges. Besides preventing saltwater intrusion and maintaining the integrity of the reservoir as a freshwater source, dam must be designed to mitigate potential seepage failure and intrusion issues. To address these concerns, this study employed numerical simulation using the SEEP/W and CTRAN/W software. The simulation was carried out to analyze seepage discharge under a vertical dam and predict potential seawater intrusion into the reservoir. The dam was examined over a ten-year period, with varying embankment widths of 10m, 20m, and 30m. The analysis considered changes in water level (ΔH) and the addition of a cut-off wall at depths of 5m, 10m, and 15m. The obtained results showed that seepage discharge rates amounted to 3,14x10-4 m3 s-1, 2,67x10-4 m3 s-1, and 2,50x10-4 m3 s-1 for embankment widths of 10m, 20m, and 30m, respectively, under a 1m level difference condition. Following this, the safety factor for piping on vertical embankment was determined as 1.10, 1.34, and 1.39 for widths of 10m, 20m, and 30m, respectively. This factor was found to increase to 4.03 when the embankment distance was widened, and a 15m deep cut-off wall was installed. It is important to note that the seawater intrusion model predicted a seawater concentration of 65,12 g m-3 at the bottom for an embankment width of 10m, while no intrusion was observed at widths of 20m and 30m with ΔH=1m. This study aims to assess potential risks of piping due to seepage and seawater contamination at the Cisadane Estuary.